Evolution of radiation-induced dermatitis treatment - Guangmei, Deng; Weishan, He; Wenya, Liu; Fasheng, Wu; Jibing, Chen (Clinical & translational oncology, 2024)
Radiation-induced skin damage (RID) is the most prevalent, significant side effect of radiotherapy (RT). Nearly 95% of patients experience moderate to severe skin reactions after receiving radiation therapy. However, criteria for acute radiation dermatitis (ARD) treatment remain unavailable. Topical agents with anti-inflammatory properties may protect the skin and facilitate tissue regeneration in patients with RID. Many of these topical agents function through nuclear factor kappa B pathway regulation. They either reduce the levels of inflammatory factors or elicit anti-inflammatory properties of their own, thus preventing oxidative stress and inflammatory responses and thus enabling RID prevention and management. Herein, we explore the 25 topical agents investigated for RID prevention and management thus far and evaluate their mechanisms of action. These agents include 11 natural agents, 3 miscellaneous agents, 9 topical nonsteroidal agents, and 2 topical corticosteroids.